2019
DOI: 10.3389/fmars.2019.00303
|View full text |Cite
|
Sign up to set email alerts
|

Functional Traits of Fish Species: Adjusting Resolution to Accurately Express Resource Partitioning

Abstract: One of the core challenges of functional diversity is the identification of traits that can accurately be linked to ecological processes. Trait-based metrics have been used to detect and quantify the effects of deterministic processes, such as niche filtering and co-occurrence mechanisms. However, most functional studies have simplified the measured attributes, especially for fish species. Here, we aimed to test the influence of trait resolution and surrogates on the accuracy in expressing resource partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Ecologists frequently use either phylogenetic or morphological similarity as a proxy for ecological similarity (Morales-Castilla, Matias, Gravel, & Araújo, 2015). However, few studies have tested these assumed relationships, and this may be due to the great effort required to obtain sufficient empirical data for large numbers of species (Silva et al, 2019). Our analysis of phylogenetic, morphological, dietary, and isotopic data for diverse tropical fish assemblages showed that morphological traits had moderate correlations with diet and weak correlations with stable isotope ratios, whereas phylogeny had weak correlations with both dietary and isotopic data.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists frequently use either phylogenetic or morphological similarity as a proxy for ecological similarity (Morales-Castilla, Matias, Gravel, & Araújo, 2015). However, few studies have tested these assumed relationships, and this may be due to the great effort required to obtain sufficient empirical data for large numbers of species (Silva et al, 2019). Our analysis of phylogenetic, morphological, dietary, and isotopic data for diverse tropical fish assemblages showed that morphological traits had moderate correlations with diet and weak correlations with stable isotope ratios, whereas phylogeny had weak correlations with both dietary and isotopic data.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of systematic methods of data collection for reef ecosystems that involve a combination of citizen scientist and academics, such as the RLS, represent a key step for advancing global biodiversity monitoring systems (Edgar et al, 2020). Lastly, we note that the coarse nature of traits selected (da Silva et al, 2019) and the large species pool (eastern Atlantic Ocean) used in the null models, might have underscored the importance of biotic mechanisms (e.g. competitive exclusion)…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate that at higher population sizes the patterns would be parallel, but it is more difficult to anticipate effects of a dynamic ecosystem that has encountered and may continue to encounter new exotic species. The success (or failure) of new invaders becoming established is a multivariate niche space question (May & Mac Arthur, 1972; Da Silva et al., 2019) and some current threats, such as ruffe, Gymnocephalus cernua (Savino & Kolar, 1996), and rudd, Scardinius erythrophthalmus (Kapuscinski et al., 2012), are under close observation for interactions with native yellow perch. Additionally, while our results were limited to mostly adult‐sized fish, ontogenetic diet changes should be examined for these species to determine how resource competition propagates through ontogeny.…”
Section: Discussionmentioning
confidence: 99%